Analysis of Environmental Management Characteristics Using Network Analysis of CEO Communication in the Automotive Industry - Yongkyu Choi (MDPI AG, 2021)
CEO messages in CEO communication are becoming increasingly important. From a sustainable management perspective, it is imperative to study environmental, social, and governance messages. Previous studies on CEO messages have focused on financial analyses. In contrast, this study (1) extracted environment-related words in the CEO messages of automotive companies, (2) selected high- and low-performing automotive manufacturers based on car sales data, (3) compared environment-related keywords used by high-performing (upper group) and low-performing (lower group) companies, and (4) performed a structural interpretation of the keywords to analyze the characteristics of environmental management. A comparison between the upper and lower groups revealed that six keywords—society, electric, technology, standards, contribute, and global—were exclusive to the upper group. The six keywords exclusive to the lower group were sales, target, promote, energy, efforts, and system. Environmental keywords and eco-innovation factors were subjected to keyword–factor mapping and network analysis. Normative pressures, technology, and environmental managerial concerns were the key factors with the highest centrality. Accordingly, the environmental management characteristics of the upper-group corporations can be used as benchmarks by lower groups.